"I Was Facilitating Everybody Else's Life. And Mine Had Just Ground to a Halt": The COVID-19 Pandemic and its Impact on Women in the United Kingdom. (12th May 2022) - Herten-Crabb, Asha; Wenham, Clare
Abstract: A growing body of research has highlighted the disproportionately negative impact of the COVID-19 pandemic on women globally. This article contributes to this work by interrogating the lived realities of sixty-four women in the United Kingdom through semi-structured in-depth interviews, undertaken during the first and second periods of lockdown associated with COVID-19 in 2020. Categorizing the data by subgroup of women and then by theme, this article explores the normative and policy-imposed constraints experienced by women in 2020 with regard to paid and unpaid labor, mental health, access to healthcare services, and government representation and consideration of women. These findings highlight women's varied and gendered experiences of the COVID-19 pandemic and emphasizes the role that government can proactively play in attending to gender inequalities throughout its COVID-19 response.